Tinjauan Pustaka: Otitis Media Akut - Angela Ramanda P.; Indah Rahmawati; Hastuti Rahmi (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Acute Otitis Media (AOM) is one of the most common pediatric ear infections and may lead to significant complications when not diagnosed and managed appropriately. This literature review aims to summarize current evidence regarding the diagnostic approach and management of AOM. A structured search was conducted through PubMed, ScienceDirect, and Google Scholar, focusing on publications from the last ten years. The diagnosis of AOM is primarily established through clinical symptoms such as otalgia, fever, and irritability, supported by otoscopic findings including middle ear effusion, tympanic membrane erythema, or bulging. Adjunctive tools such as pneumatic otoscopy and tympanometry may improve diagnostic accuracy in selected cases. Management strategies emphasize assessing disease severity to determine the need for antibiotics. Amoxicillin remains the first-line therapy, while a watchful waiting strategy is recommended for mild, uncomplicated cases. Supportive therapy, particularly analgesics, plays a crucial role in minimizing patient discomfort. In recurrent or persistent cases, evaluation of contributing risk factors such as allergic rhinitis, passive smoke exposure, and eustachian tube dysfunction is essential. This review highlights that accurate diagnosis and rational treatment selection are key to preventing complications and reducing recurrence rates in AOM.